2017
DOI: 10.1002/mas.21553
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry‐based metabolomics: Targeting the crosstalk between gut microbiota and brain in neurodegenerative disorders

Abstract: Metabolomics seeks to take a "snapshot" in a time of the levels, activities, regulation and interactions of all small molecule metabolites in response to a biological system with genetic or environmental changes. The emerging development in mass spectrometry technologies has shown promise in the discovery and quantitation of neuroactive small molecule metabolites associated with gut microbiota and brain. Significant progress has been made recently in the characterization of intermediate role of small molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 102 publications
(210 reference statements)
1
92
0
Order By: Relevance
“…Without gut microbiota, the excitability of enteric neurons would likely be attenuated, based on data observed in GF mice . Through the ENS, gut microbiota and the brain communicate bidirectionally through neural and humoral (systemic circulation) pathways (Luan et al, 2017). Parasympathetic vagus afferents carry neural information from internal organs, including the gut, to the brain (Breit et al, 2018).…”
Section: The Mgb Axis and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without gut microbiota, the excitability of enteric neurons would likely be attenuated, based on data observed in GF mice . Through the ENS, gut microbiota and the brain communicate bidirectionally through neural and humoral (systemic circulation) pathways (Luan et al, 2017). Parasympathetic vagus afferents carry neural information from internal organs, including the gut, to the brain (Breit et al, 2018).…”
Section: The Mgb Axis and Depressionmentioning
confidence: 99%
“…The decrease in Faecalibacterium, Bifidobacterium, Lactobacillus (Aizawa et al, 2016), and Dialister (Kelly et al, 2016), and increase in Clostridium, Streptococcus, Klebsiella, Oscillibacter, Allistipes (Naseribafrouei et al, 2014;Jiang et al, 2015;Lin et al, 2017;Rong et al, 2019), Eggerthella, Holdemania, Gelria, Turicibacter, Paraprevotella, and Anaerofilum (Kelly et al, 2016) genera have been found among MDD patients. This shift in the gut microbiota composition may contribute to a shift in the regulation of the host physiology (Luan et al, 2017). It is, thus, worthwhile to tackle MDD from the MGB axis standpoint, with an emphasis on the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Recent work suggests microbial disturbances linked to BA profiles are implicated in neurodegenerative disorders. [8][9][10][11][12][13] The gut microbiota are involved in immune, neuroendocrine, and neural pathways [10,11,[14][15][16][17][18], have been shown to regulate microglial maturation and function, and may contribute to AD. [18,19] Peripheral metabolic changes may influence central changes through the liver and gut-brain axis that includes commensal and pathogenic bacteria, through its interactions with the vagus nerve, changes in central nervous system functioning, the immune system [20,21], and hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, bulk omics approaches, such as proteomics and metabolomics, eliminate all spatial information, morphology, and heterogeneity, which are vital to disentangle the essence of such complex eukaryotic-prokaryotic networks. To overcome these limitations, mass spectrometry imaging (MSI) has emerged as a novel potent tool to assess the heterogeneity of a tissue at a single cell resolution [92][93][94][95]. Thus, by determining the spatial distribution and abundance of known or unknown molecular species, MSI can identify the cellular distribution of specific GMMs in the IO epithelium, the biotransformation of such compounds in metabolites, and the metabolic and/or proteomic response of intestinal cells to the compound [96].…”
Section: Strategies To Evaluate Intestinal Organoid Responses To Micrmentioning
confidence: 99%